2012
DOI: 10.2478/s11658-011-0032-x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the NFκB and glutathione pathways in mature human erythrocytes

Abstract: Abbreviations used: Ca 2+ -calcium; ERK2 -extracellular signal-regulated kinase 2; GPIIb/IIIa -glycoprotein IIb/IIIa; GSH -reduced glutathione; ICAM-1 -inter-cellular adhesion molecule; IFN-γ -interferon-γ; IκB-α -inhibitor of kappaB; IKK-α -IκB kinase-α; IL-6 -interleukin-6; IL-8 -interleukin-8; JNK1 -c-Jun N-terminal kinase 1; NFκB -nuclear factor κB; PS -phosphatidylserine; R -putative phosphatidylserine receptor Abstract: Anucleated erythrocytes were long considered as oxygen-transporting cells with limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Even in erythrocytes, NF-κB and major components of the canonical NF-κB signalling pathway interfere with the antioxidative system. Challenged by its inhibitors, compounds such as Bay 11-7082 and parthenolide, GSH levels drop, and so does erythrocyte survival (74). The examples of responses of NF-κB to GSH in vivo are numerous and specific (9,19,35,64).…”
Section: How Glutathionylation Regulates the Nf-κb And Ap-1 Signallinmentioning
confidence: 99%
“…Even in erythrocytes, NF-κB and major components of the canonical NF-κB signalling pathway interfere with the antioxidative system. Challenged by its inhibitors, compounds such as Bay 11-7082 and parthenolide, GSH levels drop, and so does erythrocyte survival (74). The examples of responses of NF-κB to GSH in vivo are numerous and specific (9,19,35,64).…”
Section: How Glutathionylation Regulates the Nf-κb And Ap-1 Signallinmentioning
confidence: 99%
“…Also, Ca 2+ stimulates cell membrane scrambling, leading to exposure of phosphatidylserine at the cell surface (Lang et al , ). The Ca 2+ ‐permeable cation channels are activated by oxidation (Duranton et al , ), and eryptosis is thus sensitive to oxidative stress (Bhavsar et al , ; Ghashghaeinia et al , , , ; Lang et al , ; Calderon‐Salinas et al , ; Maellaro et al , ). So far, all published studies concerning eryptosis were performed with unfractionated erythrocyte concentrates containing a mixture of cells with different ages.…”
mentioning
confidence: 99%
“…It is rapidly and efficiently accumulated into the RBCs, where it is converted to metformin by free thiols that exist with high amounts in the RBCs. 15 We have previously reported that the conversion of the cyclohexyl sulfenamide prodrug is very fast, half-life being less than 5 min in 1 mM GSH solution, and it liberates metformin quantitatively. 14 Because the RBSs contain high levels of GSH, it can be assumed that the conversion of the sulfenamide prodrug is relatively fast also in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the cyclohexyl prodrug of metformin seems to have ideal properties for sustained‐release purposes. It is rapidly and efficiently accumulated into the RBCs, where it is converted to metformin by free thiols that exist with high amounts in the RBCs . We have previously reported that the conversion of the cyclohexyl sulfenamide prodrug is very fast, half‐life being less than 5 min in 1 mM GSH solution, and it liberates metformin quantitatively .…”
Section: Discussionmentioning
confidence: 99%